Adaptació escolar, actituds i aprenentatge del català en l'alumnat de les aules d'acollida de Primària i Secundària a Catalunya (2005-2006) - Serra, Josep M.; Perera, Santiago; Siqués, Carina; Mayans, Pere; Canal, Imma (Caplletra. Revista Internacional de Filologia, 2008)
In the last years a very important amount of immigrant students unaware of Catalan, a language typical of the educational system of Catalonia, have arrived to Catalonia. To face this situation an organizational educative model, known asnewcomers classrooms, was started in 2003. It aims at speeding up the access of immigrant students to Catalan conversational uses in order to facilitate their school integration.This article presents a study that evaluates the results of newcomers classrooms, using as data the whole number of students that attended them in the course 2005-2006: 10.043 pupils of primary education (of 591 schools) and 6.474 pupils ofsecondary education (of 332 secondary schools). For the research two sets of tests were used: one about the knowledge of Catalan and another one about integration and school adaptation.The results show that newcomers classrooms’ students manage to learn the Catalan language, but also show that there are differences between the several linguistic collectives, due to, among other factors, the attitudes towards the school institutionand their self-esteem, as well as to the particular characteristics of their initial language.The study demonstrates that all these factors are related. In consequence, the explanation of the differences about the knowledge of Catalan can not be made from isolated factors but from their interaction.